Summer and winter precipitation in East Asia scale with global warming at different rates - Wengui Liang (Nature Portfolio, 2021)
Precipitation responses to climate warming in East Asia differ between summer and winter as a result of steepening atmospheric moisture gradients, weakening westerlies and a higher hydrological amplitude in atmospheric eddies, according to climate model simulations.